2020
DOI: 10.1002/suco.202000020
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and durability studies on high‐volume fly‐ash concrete

Abstract: This article presents the experimental results on accelerated carbonation‐induced corrosion and related durability properties such as AC impendence, half‐cell potential, water permeability, and volume of permeable voids test of concrete made with high‐volume Class F fly ash (FA). Concrete specimens were prepared by substituting ordinary portland cement with FA at varying replacement levels (0–70%). High‐volume FA concrete shows the continuous gain in the compressive strength and ultrasonic pulse velocity over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“…SEM analysis in the study by Barbara et al [30] distinctly showed intermixing of Fe and Al-Si mineral phase along with the predominance Ca non-silicate materials in the case of class F fly ash as pozzolanic material with low Ca. About general chemical and physical characteristics and elemental composition of this fly ash type, Kumar et al [34] carried out SEM analysis on OPC and FA to explore the morphology of concrete specimens. SEM results demonstrated that OPC particles are more irregular compared to FA particles, which are in spherical shapes, as shown in Figure 2.…”
Section: Scanning Electron Microscopy (Sem)mentioning
confidence: 99%
“…SEM analysis in the study by Barbara et al [30] distinctly showed intermixing of Fe and Al-Si mineral phase along with the predominance Ca non-silicate materials in the case of class F fly ash as pozzolanic material with low Ca. About general chemical and physical characteristics and elemental composition of this fly ash type, Kumar et al [34] carried out SEM analysis on OPC and FA to explore the morphology of concrete specimens. SEM results demonstrated that OPC particles are more irregular compared to FA particles, which are in spherical shapes, as shown in Figure 2.…”
Section: Scanning Electron Microscopy (Sem)mentioning
confidence: 99%
“…It is an extremely popular mineral mixture that is only available in states with coal-burning facilities. In this study [3], concrete specimens were made with various mix ratios (0-70 percent) instead of normal Portland cement using FA. The steady increase in compressive strength and pulse velocity over 365 days is reflected in the high-volume FA concrete.…”
Section: Introductionmentioning
confidence: 99%
“…The usage of fly ash to partially replace cement in the total mix is capable of improving the segregation and the strength of concrete [21,22]. Substituting cement with fly ash delivers impactful economic and environmental benefits, as less manufacturing of cement reduces the cost and the carbon footprint to the environment [23][24][25].…”
Section: Introductionmentioning
confidence: 99%